Solving an enigma in the tree of life, at the origins of teleost fishes - Parey, Elise; Berthelot, Camille; Roest Crollius, Hugues; Guiguen, Yann (Comptes Rendus Biologies)
Tracing the phylogenetic relationships between species is one of the fundamental objectives of evolutionary biology. Since Charles Darwin’s seminal work in the 19th century, considerable progress has been made towards establishing a tree of life that summarises the evolutionary history of species. Nevertheless, substantial uncertainties still remain. Specifically, the relationships at the origins of teleost fishes have been the subject of extensive debate over the last 50 years. This question has major implications for various research fields: there are almost 30,000 species in the teleost group, which includes invaluable model organisms for biomedical, evolutionary and ecological studies. Here, we present the work in which we solved this enigma. We demonstrated that eels are more closely related to bony-tongued fishes than to the rest of teleost fishes. We achieved this by taking advantage of new genomic data and leveraging innovative phylogenetic markers. Notably, in addition to traditional molecular phylogeny methods based on the evolution of gene sequences, we also considered the evolution of gene order along the DNA molecule. We discuss the challenges and opportunities that these new markers represent for the field of molecular phylogeny, and in particular the possibilities they offer for re-examining other controversial branches in the tree of life.